Feasibility Study on Performance of Heat Exchanger-001 Refinery in Pusat Pengembangan Sumber Daya Manusia MIGAS Cepu - E Saputro; R A Santoso; N N Saraswati (BIOMEJ, 2022)
PPSDM Migas Cepu is one of oil and gas industry in Indonesia. Their process requires Heat Exchanger for pre-heating purposes. The Heat Exchanger cannot work optimally because of the impurities attached to the walls shell and tube. Sometime the impurities attached to the walls of shell and tube, so it makes can’t work optimally of this industry. For that reason, the purpose of this calculation is to find out the heat efficiency during the process. Heat efficiency is the ratio of the amount of heat that moves from a high temperature fluid to a lower temperature fluid in a certain time unit which can show the performance of a Heat Exchanger. The result show that the clean overall coefficient (Uc) and design overall coefficient (Ud) are 7,4301 Btu/ft2.jam.oF and 7,2517 Btu/ft2.jam.oF. For dirt factor (Rd) are 0,0033 ft2.jamoF/Btu. The Pressure Drop are 0,0448 Psi for Tube and 0,0035 Psi for Shell. The value of the Heat Efficiency are 82,3840 %. Which mean according to the results of these parameters, it can be concluded that the Heat Exchanger-001 is still possible to operate.